Mortality risk in patients with myasthenia gravis - Khateb, Mohamed; Shelly, Shahar (Frontiers in Neurology, 2025)
IntroductionAlthough some reports link Myasthenia Gravis to higher mortality, the evidence remains contradictory and unclear. Real-life data is limited primarily due to challenges in selecting control groups and mitigating bias. Additionally, a revised mortality assessment should be conducted due to recent advancements in Myasthenia Gravis treatments over the past decade, including new biological therapies and the impact of the COVID-19 pandemic from 2020 to 2023.MethodsWe conducted a retrospective analysis of all patients diagnosed with Myasthenia Gravis at our tertiary center between 2000 and 2023, extracting mortality and clinical features compared to two age- and sex-matched control groups of neurological or rheumatologic patients.ResultsWe identified 436 Myasthenic patients and 2,616 controls (1308 in each control group). Myasthenia Gravis mortality was 14% at 5 years (61/422) and 21% at 10 years (87/422). Mortality was significantly higher than control groups (p < 0.001). Intubations during myasthenic crisis were linked to higher mortality (p = 0.002). Bulbar weakness at presentation showed higher mortality but did not reach clinical significance. We compared the mean age at death in MG patients to national life expectancy benchmarks using a one-sample Z-test, revealing significantly younger age at death in both males (78.3 vs. 81.6 years, p = 0.009) and females (76.5 vs. 85.2 years, p < 0.00001). Patients with normal thymic pathology showed better outcomes and lower mortality after thymic removal (p < 0.0001). The primary cause of death was linked to infections, significantly correlated with chronic steroid use.DiscussionIn conclusion, patients with Myasthenia Gravis had higher mortality rates. Thymic removal reduced mortality, while intubation is associated with increased mortality risk.